Fatigue design of components - Marquis, G. (Gary); Solin, J. (ESIS publication)
This volume contains a selection of papers presented at Fatigue Design 95 held in Helsinki, Finland from 5-8 September 1995. The papers have been peer reviewed and present practical aspects for the design of components and structures to avoid fatigue failure. Topics covered include: fatigue design experiences, ground vehicle components, component reliability, multiaxial fatigue, notch analysis, service loading, welded structures, probabilistics aspects in fatigue, fatigue design optimization.